Technical Translation Training in Groups of Foreign Students Using Multimedia-based Project Activities; Procedia - Social and Behavioral Sciences; Vol. 215 : International Education and Cross-Cultural Communication, Problems and Solutions, (IECC 2015) - Tereshkova N. S. Nadezhda; Gural S. K. Svetlana; Tikhonova E. V. Evgeniya; Kalinina E. W. Elena Wladimirowna (2015, 2015)
Title screen